Flow cytometry-sorted non-viable endotoxin-treated human monocytes are strongly procoagulant - Henriksson, Carola E.; Hellum, Marit; Landsverk, Kirsti S.; Klingenberg, Olav; Joø, Gun-Britt; Kierulf, Peter (Thrombosis and Haemostasis, 2006)
Monocytes/macrophages are important in disease states such as gram-negative sepsis and coronary artery disease. Following exposure to lipopolysaccharide (LPS), monocytes express tissue factor (TF), the main initiator of blood coagulation. We previously demonstrated that human monocytes treated with high concentrations of LPS, or with LPS and calcium ionophore, displayed higher TF activity than monocytes treated with only low concentrations of LPS, even though the monocytes under all conditions expressed similar amounts of cell surface TF antigen. Such restrained TF activity is often referred to as encryption and its release as de-encryption. We also observed that the increase in TF activity, de-encryption, coincided with an increase in cell surface phosphatidylserine (PS) representing apoptosis and necrosis. In the present work, we separated LPS and LPS and calcium ionophore-treated human monocytes into two populations, one of mainly viable, PS negative cells, and one of mainly non-viable, PS positive cells, by sorting flow-cytometry. We observed that non-viable cells expressed considerably less TF antigen than viable cells. Despite this, non-viable cells were clearly more procoagulant than viable cells in two different coagulation assays. Procoagulant activity was dependent on both TF and PS. We consider the higher content of externalized PS in non-viable monocytes as the major reason for the stronger procoagulant activity of these cells. Thus, TF de-encryption appears largely to occur on PS positive, non-viable cells under these conditions. This supports the important role of PS in coagulation, and it suggests that PS expression signifying cell death, may be clinically relevant.
Keywords: Tissue factor; coagulation; phosphatidylserine; monocyte; sorting flow cytometry